Peningkatan Literasi Geospasial Siswa Melalui Pelatihan Google Earth Di SMAN 2 Konawe Selatan - Wa Ode Samlia; Sunarty Suly Eraku; Nurfaika Nurfaika (Universitas Negeri Gorontalo, 2026)
Digital transformation demands a shift in Geography learning from theoretical memorization to the mastery of practical spatial skills. This community service aims to improve the geospatial literacy of SMAN 2 Konawe Selatan students through Google Earth training for determining coordinate points. The method applied was a participatory training based on direct practice, which included concept reinforcement, demonstrations, independent/group practice, and evaluations using pretest and posttest. The results of the service showed a significant increase in geospatial literacy, where the students' average score jumped from 62 (pretest) to 86 (posttest) with an N-Gain value of 0.63 (medium category). Furthermore, as many as 86.7% of students successfully determined the coordinate points of contextual locations with precision through worksheets. In conclusion, Google Earth training is effective as an interactive learning medium that bridges theory and spatial practice for students.